Tinjauan Hukum Terhadap Pinjam Pakai Nama Untuk Sertifikat Hak Milik Di Kota Pekanbaru - Audesti Nindya; Firdaus Firdaus; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Along with the development of the land age is not only used as a land of settlement and agriculture, but the land has an important role in the economic development of the community. Land is one of the fixed assets that has a very important function and role for humans. Land issues in the era of development are indeed increasingly complicated and potentially causing turmoil. The complicated issue also arises in one case in the Pekanbaru City District Court, the problem arises because the plaintiff borrowed the name of the defendant without making an agreement. The essence of the problem is on borrowing using the name, borrowing using the name does not exist in the civil law order specifically, whether material or formal. The purpose of the writing of this thesis is First, to find out how to give a certificate of land ownership in the city of Pekanbaru. Second, to find out how the legal status of the land title certificate is based on borrowing, using the name given by the Pekanbaru City Land Agency. From the results of the research problem there are two main things that can be concluded. First, the community must go through several stages to obtain ownership rights on the land, in several stages the researcher did not find out about the method or procedure for making a loan based on the name. Borrow using names for property rights certificates is carried out to acquire land above the maximum stipulations set by the government. Borrowing using names for property rights certificates is done to invest his property in the land in order to obtain multiple profits. Second, the legal status of the land which is certified based on the name and use of the loan is valid with the ownership of the land is the person whose name is on the certificate and so the responsibility for all legal actions against the land that is responsible is the person whose name is listed on the certificate not the person who borrow or use names.Keywords: Legal Review-Borrowing Using Ownership Rights